The ethics of biomedical big data - Mittelstadt, Brent Daniel; Floridi, Luciano (Law, governance and technology series, 2016)
Intro -- Contents -- Contributors -- Introduction -- 1 Background -- 2 Big Data -- 3 Biomedical Big Data -- 4 Structure of the Volume -- 4.1 Part I: Balancing Individual and Collective Interests -- 4.2 Part II: Privacy and Data Protection -- 4.3 Part III: Consent -- 4.4 Part IV: Ethical Governance -- 4.5 Part V: Professionalism and Ethical Duties -- 4.6 Part VI: Foresight -- References -- Part I Balancing Individual and Collective Interests -- "Strictly Biomedical? Sketching the Ethics of the Big Data Ecosystem in Biomedicine" -- 1 The Chiaroscuro Portrait of Big Data -- 2 Typical Big Biomedical Data -- 3 Non-biomedical Big Data of Great Biomedical Value -- 3.1 Loyalty Cards Points -- 3.2 Social Media -- 3.3 Mobile Devices -- 4 The Digital Phenotype -- 5 Towards a New Ethical Framework -- 5.1 Vision for a New Framework -- 5.2 Design Requirements -- 5.3 Substantive Key Elements -- 5.3.1 (1) Ethical Use and Privacy -- 5.3.2 (2) Data Governance -- 5.3.3 (3) Transparency and Accountability -- 6 Conclusion -- References -- Using Transactional Big Data for Epidemiological Surveillance: Google Flu Trends and Ethical Implications of `Infodemiology' -- 1 Introduction -- 2 A Pragmatist Approach to Ethics -- 3 Historical Overview -- 3.1 Infodemiology: Covering `Supply' and `Demand' -- 3.2 Analysing Health Information Demand -- 4 Case Study: Google Flu Trends -- 4.1 Normative Assumptions, Justifications and Values -- 4.1.1 Epidemics of Fear -- 4.1.2 The `Innocent User' as Ideal Data Source -- 4.1.3 Privacy -- 4.2 Discourse Ethics -- 4.2.1 Institutional Context -- 4.2.2 Stakeholder Analysis -- 5 Conclusion -- References -- Denmark at a Crossroad? Intensified Data Sourcing in a Research Radical Country -- 1 Introduction -- 2 From Data Mining to Intensified Data Sourcing -- 3 Denmark: A Country at a Crossroad -- 3.1 The Register Infrastructure.
Description based upon print version of record
Keywords: Electronic books; Medizinische Ethik; Biomedizin; Big Data